2010
DOI: 10.1166/jctn.2010.1541
|View full text |Cite
|
Sign up to set email alerts
|

Unitary Reflection Groups for Quantum Fault Tolerance

Abstract: Abstract.This paper explores the representation of quantum computing in terms of unitary reflections (unitary transformations that leave invariant a hyperplane of a vector space). The symmetries of qubit systems are found to be supported by Euclidean real reflections (i.e., Coxeter groups) or by specific imprimitive reflection groups, introduced (but not named) in a recent paper [Planat M and Jorrand Ph 2008, J Phys A: Math Theor 41, 182001]. The automorphisms of multiple qubit systems are found to relate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 44 publications
(108 reference statements)
0
29
0
Order By: Relevance
“…It is found to be of type G 4 . The representation of index 1120 and rank four of O 7 (3) found in the Atlas is associated with the dual of W 5 (3) that is the dense near hexagon DQ (6,3). See below Table 9 for further details.…”
Section: Orthogonalmentioning
confidence: 99%
See 3 more Smart Citations
“…It is found to be of type G 4 . The representation of index 1120 and rank four of O 7 (3) found in the Atlas is associated with the dual of W 5 (3) that is the dense near hexagon DQ (6,3). See below Table 9 for further details.…”
Section: Orthogonalmentioning
confidence: 99%
“…The representation of index 560 of rank 17 and sub-degrees 1, 13 3 , 26 6 , 52 7 leads to a configuration of type [560 13 , 1820 4 ] (i.e., every point is on 13 lines, and there are 1820 lines of size four). The Atlas also provides a representation of index 1456 and rank 79 that leads to another geometry, of order (3,4), with again 1820 lines of size four (see also the relevant item in Table 10). The physical meaning of both representations, if any, has not been discovered.…”
Section: Exceptional and Twistedmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last years, it has been recognized that the detailed investigation of commutation between the elements of generalized Pauli groups -the qudits and arbitrary collections of them [1]-is useful for a better understanding of concepts of quantum information such as error correction [2,3], entanglement [4,5] and contextuality [6]- [8], that are cornerstones of quantum algorithms and quantum computation. Only recently the first author observed that much of the information needed is encapsulated in permutation representations, of rank larger than two, available in the Atlas of finite group representations [9].…”
Section: Introductionmentioning
confidence: 99%